PENGARUH PENAMBAHAN MCKENZIE EXERCISE PADA PEMBERIAN MUSCLE ENERGY TECHNIQUE TERHADAP KELUHAN NYERI LEHER KARYAWAN PT. ISKANDARTEX: THE INFLUENCE OF MCKENZIE EXERCISE ADDITION TO MUSCLE ENERGY TECHNIQUE ON NECK PAIN COMPLAINTS - Dwi Sari Kusumaningrum; Suhardi; Sukadarwanto (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2025)
Background: Work performed in certain positions such as factory workers for a long time and continuously can cause static loading on the neck muscles to increase. Increased static loads that occur continuously can result in increased muscle tone which in the long term will cause neck pain. Objective: Knowing the effect of adding McKenzie Exercise to the provision of Muscle Energy Technique on neck pain complaints of PT Iskandartex employees. Method: This study used a two groups pre-test and post-test design. Subjects are employees of PT Iskandartex who fit the inclusion criteria. Subjects totaled 30 people who were divided into 2 groups consisting of 15 people each group and intervened for 12 sessions in 4 weeks. Group I will be given Muscle Energy Technique intervention plus McKenzie Exercise and group II will be given Muscle Energy Technique intervention. The pain measurement tool used is QVAS at the beginning and end of the intervention. Results: Based on the results of statistical analysis tests before and after intervention in group obtained p= 0.000 (p <0.05) which means there is an effect. In group B II obtained p= 0.000 (p<0.05) which means there is an effect. the results of hypothesis testing after treatment of groups and II obtained results p= 0.000 (p<0.05) which means there is a difference in effect Conclusion: The addition of McKenzie Exercise to the provision of Muscle Energy Technique can reduce neck pain complaints in employees of PT Iskandartex.